Plasmonic evolution of atomically size-selected Au clusters by electron energy loss spectrum. Issue 12 (25th November 2020) - Lu, Siqi; Xie, Lin; Lai, Kang; Chen, Runkun; Cao, Lu; Hu, Kuojuei; Wang, Xuefeng; Han, Jinsen; Wan, Xiangang; Wan, Jianguo; Dai, Qing; Song, Fengqi; et al.
Abstract: The plasmonic response of gold clusters with atom number ( N ) = 100–70 000 was investigated using scanning transmission electron microscopy-electron energy loss spectroscopy. For decreasing N, the bulk plasmon remains unchanged above N = 887 but then disappears, while the surface plasmon firstly redshifts from 2.4 to 2.3 eV above N = 887 before blueshifting towards 2.6 eV down to N = 300, and finally splitting into three fine features. The surface plasmon's excitation ratio is found to follow N 0.669, which is essentially R 2 . An atomically precise evolution picture of plasmon physics is thus demonstrated according to three regimes: classical plasmon ( N = 887–70 000), quantum confinement corrected plasmon ( N = 300–887) and molecule related plasmon ( N < 300). Abstract : Through the plasmonic investigation of atomically-precision gold nanoparticles, a complete evolution picture linking classical solid-state physics to quantum confinement corrected plasmon and to quantized molecular-like physics is constructed with two atomic precision transition points.